Prevalence of and factors associated with current asthma symptoms in school children aged 6-7 and 13-14 yr old in Bogotá, Colombia (2008)
This cross‐sectional study of children aged 6–7 years and adolescents aged 13–14 years in Bogotá, Colombia, assessed the prevalence of asthma symptoms and their associations with dietary, health, and behavioral habits. This study is part of the International Study of Asthma and Allergies in Childhood (ISAAC)‐phase III. Asthma prevalence among the children was assessed using a parental self‐administered written questionnaire (WQ), and among adolescents using a WQ together with a video questionnaire (VQ). Associations were estimated with bivariate and multivariate analysis. The study found that the 6–7 year age‐group were more likely to report current asthma symptoms than the 13–14 year age‐group (10.4% [WQ] vs. 8.6% [WQ] and 8.0% [VQ], respectively). Factors associated with current asthma symptoms among the 6–7 year age‐group included higher maternal education (OR = 1.7, [95% CI 1.2–2.6], p = 0.007), a cat in the home during the last year (OR = 1.5, [95% CI 1.0–2.3], p = 0.036), watching TV 1–2 hours/day (OR = 2.1, [95% CI 1.2–3.9], p = 0.013), and medication with acetaminophen in the first and most recent year of life (OR = 1.8, [95% CI 1.3–2.4], p < 0.001; OR = 2.2, [95% CI 1.7–2.8], p < 0.001, respectively) or antibiotics in the first year of life (OR = 1.9, [95% CI 1.4–2.5], p < 0.001). Among the 13–14 year age‐group, factors associated with current asthma symptoms included medication with acetaminophen during the last year (OR = 1.8, [95% CI 1.4–2.3], p < 0.001); cereal, milk, and fruit consumption 3 or more times weekly (OR = 1.5, [95% CI 1.1–1.9], p = 0.010; OR = 0.8, [95% CI 0.6–1.0], p = 0.046; OR = 0.6, [95% CI 0.4–1.0], p = 0.031, respectively). Overall, compared with that in other Latin American centers, asthma prevalence in Bogotá is close the lower estimates. However, associations with dietary, health, and behavioral habits need further study to assess their complex relationship with asthma.